2016
DOI: 10.1002/anie.201608181
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Direct Synthesis of Endocyclic Vicinal Diamines through Chiral Ru(diamine)‐Catalyzed Hydrogenation of 2,2′‐Bisquinoline Derivatives

Abstract: An asymmetric hydrogenation of 2,2'-bisquinoline and bisquinoxaline derivatives, catalyzed by chiral cationic ruthenium diamine complexes, was developed. A broad range of chiral endocyclic vicinal diamines were obtained in high yields with excellent diastereo- and enantioselectivity (up to 93:7 dl/meso and >99 % ee). These chiral diamines could be easily transformed into a new class of chiral N-heterocyclic carbenes (NHCs), which are important but difficult to access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 103 publications
0
22
0
5
Order By: Relevance
“…Fan et al also reported the asymmetric hydrogenation of 2,2'-bisquinolines to form vicinal diamines using a series of [arene/Ru/TsDPEN] catalysts including 14-16 [21] (Figure 11). In several cases, the N'-methylated catalyst proved to be the best one in the application, although in others the unmethylated complex was better.…”
Section: Rumentioning
confidence: 99%
“…Fan et al also reported the asymmetric hydrogenation of 2,2'-bisquinolines to form vicinal diamines using a series of [arene/Ru/TsDPEN] catalysts including 14-16 [21] (Figure 11). In several cases, the N'-methylated catalyst proved to be the best one in the application, although in others the unmethylated complex was better.…”
Section: Rumentioning
confidence: 99%
“…Asymmetric hydrogenation has proven to be one of the most powerful methods for the preparation of various chiral amines . However, examples of the direct synthesis of chiral vicinal diamines by catalytic asymmetric hydrogenation are extremely rare . Previously, we demonstrated that the cationic ruthenium or iridium complexes of chiral monosulfonated diamines are excellent catalysts in the asymmetric hydrogenation of quinoline derivatives and ketimines .…”
Section: Figurementioning
confidence: 63%
“…Such chiral NHCs could be readily accessed through the direct derivatization of vicinal diamines . However, to the best of our knowledge, the direct catalytic asymmetric synthesis of sterically hindered N , N′ ‐diaryl vicinal diamines has not been achieved …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…A novel method to obtain optically pure chiral endocyclic vicinal diamines have been demonstrated by Fan and coworkers. 34 In this protocol, the chiral cationic ruthenium diamine catalyst 19 has been applied to the AH of 2,2′-bisquinoline and 2,2′-bisquinoxaline derivatives to give the corresponding chiral amines in good diastereoselectivity (up to 93 : 7) and excellent enantioselectivity (>99% ee) ( Fig. 29).…”
Section: Ruthenium-catalysed Imine Ahmentioning
confidence: 99%